(-7)+(-8)=

Simple and best practice solution for (-7)+(-8)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-7)+(-8)= equation:


Simplifying
(-7) + (-8) = 0
-7 + (-8) = 0
-7 + -8 = 0

Combine like terms: -7 + -8 = -15
-15 = 0

Solving
-15 = 0

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 21n^2-27=7n+1 | | 4x+2=20-8x | | -3x+1y=2 | | -5+y=4 | | 6b^2+5b+5b-3b-10= | | 4x+2=.5x+17 | | 6+4x=9x-20 | | -5.5a=15.5 | | (7+z)(2z+3)=0 | | -4-7(1+6r)=325 | | (-4-3x)*-8= | | 124x^2-210=25x | | 12x-13=-6x+17 | | 5(x+4)-(2x-7)=0 | | 12x-13=.5x+17 | | 4(x-2)+10=42 | | 7(y-1)=3(y+.66) | | e^6x=3.8 | | 2/3(12x-21)=90 | | 5x-y=150 | | -32/-9=8/b | | 2/7x=36 | | X+15+2x+34=13 | | 2y+6=5(y+.6) | | (1/2)(x-8)=(-2/3)(6-9x) | | 2k=5k-9 | | (4n^2+1)+(5-n^2)= | | a+6+3a=5 | | -2a-a=39 | | -2(d+6)=0 | | 3a-4.5=4.8 | | m/8=5/12 |

Equations solver categories